The Impact of Accountability on Balanced Scorecard Performance of Village-Owned Enterprises: The Mediating Role of Business Model - Rudy Suryanto; Hafiez Sofyani; Rahmat Darmawan; Tiyas Puji Utami (Jurnal Ilmiah Akuntansi, 2025)
This study investigates the effect of accountability on the performance of Village-Owned Enterprises (VOEs), with Business Model Innovation (BMI) positioned as a mediating dynamic capability. Data were collected from 104 VOEs through key organizational actors, including directors, secretaries, and treasurers who are directly involved in strategic decision-making. Organizational performance is conceptualized using the Balanced Scorecard framework as a set of performance indicators covering four dimensions: financial, customer, internal business processes, and learning and growth. Drawing on Legitimacy Theory and Dynamic Capability Theory, this study examines how accountability functions as a governance mechanism to secure organizational legitimacy, while BMI enables VOEs to transform legitimacy-driven accountability into sustainable performance outcomes amid regulatory, technological, and environmental changes. The findings indicate that accountability has a positively effect on non-financial performance dimensions and strongly stimulates BMI. However, its impact on financial performance is not direct and is fully mediated by BMI, suggesting that accountability contributes to financial outcomes only when supported by innovation-oriented capability development. These results highlight that compliance-based accountability alone is insufficient to generate measurable financial performance without strategic transformation through BMI. By integrating legitimacy and dynamic capability perspectives within the context of social entrepreneurship, this study provides theoretical contributions to governance and innovation literature and offers practical implications for VOEs by emphasizing innovation-driven accountability, balanced performance indicators, and capability development as key pathways toward sustainable rural economic development and strengthened stakeholder trust.